Factors affecting the failure of exclusive breastfeeding practice: a scoping review - Sulasmi Sulasmi; Mufdlilah Mufdlilah; Luluk Rosyida (Universitas Aisyiyah Yogyakarta, 2021)
Background: In some countries, exclusive breastfeeding is practiced in a limited number of cases and for a short period of time; on an international scale in 2012, only 39% of six-month-old babies were exclusively breastfed. This breastfeeding rate falls short of the World Health Organization's recommended threshold (WHO). According to WHO, to reach the global level by 2025, which is 50% of mothers must exclusively breastfeed for 6 months after giving birth, a strategy must be developed to encourage and facilitate the initiation and continuation of breastfeeding. So, it is hoped that with the target set by WHO, mothers can give breast milk exclusively to their babies for 6 months optimally. Exclusive breastfeeding (ASI) is the ideal nutrition for babies in the first 6 months of life, with continued breastfeeding being recommended for up to 2 years of age. The health benefits of self-feeding are dose dependent, and infants with longer periods of exclusive breastfeeding have better health outcomes. The benefits of breastfeeding are dose dependent, and children have better health outcomes when they are breastfeeding exclusively for longer periods of time, but exclusive breastfeeding has not yet reached its aim due to a variety of factors that contribute to failure.Objectives: To identify factors affecting the failure of exclusive breastfeeding practice.Method: The method employed was scoping review, which starts with identifying scoping review questions using the PEO’S framework; selecting relevant articles based on inclusion and exclusion criteria; and finally, evaluating the results. utilizing databases such as Pubmed, Willey Online Library, ProQuest, and Google Scholar to conduct literature searches; Select articles with a PRISMA Flowchart that describes the search process; execute data charting and critical appraisal; compile and report results.Result: 10 relevant articles have grade A and grade B out of the 103 items that were selected using confidence. Quantitative and qualitative research were used to create these articles. Several factors that influence the inability of exclusive breastfeeding include education knowledge, age parity, nipple pain, workplace, work facilities, workload, support culture.Conclusion: Internal and external factors influence the success of exclusive breastfeeding, the internal aspects including education and knowledge, age and parity, and nipple pain. Workplace, work facilities, workload, support, and culture all are external factors. The failure of exclusive breastfeeding is influenced by several internal and external factors Therefore, it is hoped that the second factor can be a concern to reduce the incidence of unsuccessful exclusive breastfeeding.